2021
DOI: 10.1186/s12888-021-03223-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of criminal convictions in Norwegian adult ADHD outpatients and associations with ADHD symptom severity and emotional dysregulation

Abstract: Objectives Attention deficit hyperactivity disorder (ADHD) often co-occurs with antisocial behaviour. Several studies have shown high rates of ADHD among prisoners. However, the prevalence of crime among individuals with ADHD is less known. The aim of the present study was to estimate the prevalence of lifetime criminal conviction (CC) in a clinical sample of adults with ADHD, and the associations with the severity of ADHD and emotional dysregulation (ED). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…When the criteria were not clear, the inclusion or exclusion of the article was decided among all three authors. S1 Table shows the bibliometric properties of the included articles [13,[51][52][53][54][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], which are marked with � in the references section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the criteria were not clear, the inclusion or exclusion of the article was decided among all three authors. S1 Table shows the bibliometric properties of the included articles [13,[51][52][53][54][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], which are marked with � in the references section.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies found that emotion dysregulation was significantly associated with impulsivity [13], executive function deficits and functional impairment [66]; as well as total Adult ADHD Self-Report Scale Symptom Checklist (ASRSv1.1) score with non-adaptative cognitive strategies [63]. High scores of emotion dysregulation were also associated with substance use disorder [64], criminal conviction [67], BPD comorbidity [62,63] and sluggish cognitive tempo comorbidity [66], as well as recall of parental ADHD symptoms [65]. However, no significant differences were found between ADHD emotional dysregulation scores and other disorders such as autism spectrum disorder [59].…”
Section: Emotion Regulation Features In Adult Adhdmentioning
confidence: 99%
“…Several studies have estimated that the prevalence of ADHD among male inmates ranges from 15% to 50%, and as high as 40% among female inmates. Legal studies on offences conducted in Great Britain show that 14% are long-term, which also poses a greater risk of repeated crime (Anker et al, 2021). Recidivism among persons with mental health problems and sane criminals is also similar.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined associations between the severity of ADHD features and delinquent behaviours, but have usually focused on adolescents and young adults, offenders or psychiatric outpatients (Anker et al., 2021; Barkley et al., 2004; González et al., 2016; Murray et al., 2021). A few studies test even narrower relationships, for example, focusing on circumscribed types of criminal behaviour, such as cyber deviance (Panagiotidi & Overton, 2021).…”
Section: Introductionmentioning
confidence: 99%